Die hard 2 [videorecording (DVD)] - Harlin, Renny; Willis, Bruce, 1955-; Bedelia, Bonnie, 1946-; Atherton, William; Amos, John, 1939-; Nero, Franco (Twentieth Century Fox Home Entertainment, 2004)
On a snowy Christmas Eve in Washington D.C., a team of terrorists has seized a major international airport, and now holds thousands of holiday travellers hostage. The terrorists, a renegade band of crack military commandos led by a murderous rogue officer, have come to rescue a drug lord from justice. They've prepared for every contingency - except John McClane, an off-duty cop seized by a feeling of deadly déjà vu.